2011
DOI: 10.3343/kjlm.2011.31.4.282
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of an Automated Repetitive Sequence-based PCR Microbial Typing System with IS6110-Restriction Fragment Length Polymorphism for Epidemiologic Investigation of Clinical Mycobacterium tuberculosis Isolates in Korea

Abstract: Tuberculosis remains a severe public health problem worldwide. Presently, genotyping is used for conducting epidemiologic and clinical studies on tuberculosis cases. We evaluated the efficacy of the repetitive sequence-based PCR (rep-PCR)-based DiversiLab™ system (bioMérieux, France) over the IS6110-restriction fragment length polymorphism analysis for detecting Mycobacterium tuberculosis. In all, 89 clinical M. tuberculosis isolates collected nationwide from Korea were used. The DiversiLab system allocated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…1). Jang et al (27) previously suggested that DL discriminates efficiently among Beijing family strains with near-identical IS6110-RFLP patterns, in contrast with our data which rather suggest that DL is not reliable for analysis of Beijing strains. Finally, regarding the six epidemiologically unlinked T2-T3 (SIT73) isolates S46 to S51 (Table 1), the high similarity (97%) observed within the single cluster as found with DL was not consistent with the significant differences observed in their MIRU codes and especially their RFLP patterns (Fig.…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…1). Jang et al (27) previously suggested that DL discriminates efficiently among Beijing family strains with near-identical IS6110-RFLP patterns, in contrast with our data which rather suggest that DL is not reliable for analysis of Beijing strains. Finally, regarding the six epidemiologically unlinked T2-T3 (SIT73) isolates S46 to S51 (Table 1), the high similarity (97%) observed within the single cluster as found with DL was not consistent with the significant differences observed in their MIRU codes and especially their RFLP patterns (Fig.…”
contrasting
confidence: 99%
“…The DiversiLab (DL) microbial typing system (bioMérieux, Marcy l'Etoile, France) (18) consists of a semiautomated highly standardized rep-PCR (18,19). Studies reporting on DL performance in the analysis of mycobacteria are scarce and have been done with specific aims, e.g., rapid genotyping of nontuberculosis mycobacteria (20)(21)(22)(23)(24), analysis of M. tuberculosis microevolution within a patient (25), monitoring of TB outbreaks (1,3,26), and comparison of DL to other molecular techniques for M. tuberculosis typing (1,19,27,28).…”
mentioning
confidence: 99%
“…Data generated with this method showed high concordance with those generated by IS6110-RFLP and IS1245-RFLP typing for M. tuberculosis and MAC strains, respectively (410). This method was also able to discriminate between M. tuberculosis Beijing strains whose IS6110-RFLP patterns were nearly identical (411). More recently, automated rep-PCR was applied for typing of M. abscessus and compared with the PFGE method.…”
Section: Methods Based On Repetitive Sequencesmentioning
confidence: 99%
“…In the study conducted by Noguti et al (2010), there were two isolates. Cangelosi et al (2004), Ashworth et al (2008) and Jang et al (2011) evaluated the utility of a commercially available rep-PCR System, initially developed for genotyping Streptococcus pneumoniae, Staphylococcus aureus, Enterobacteriaceae and others microorganism, to genotype M. tuberculosis and Mycobacterium avium Complex and found the system to be highly discriminative.…”
Section: Discussionmentioning
confidence: 99%